The Impact of Modern Technology on Social Research Methods in Educational Contexts - Aljounid, Horia (International Journal of Education and Teaching Zone, 2025)
This study investigates the impact of modern technology on social research methods within educational contexts, with a focus on how digital tools influence data collection, analysis, and interpretation processes. Employing a quantitative research design, a survey was conducted with 200 educational researchers and educational employees in Yemen (K-12 education, higher education, educational policy) at Taiz city, Yemen, exploring their use of technologies such as social media analytics, big data tools, and digital surveys. The findings reveal that frequent use of technology significantly enhances research efficiency and data accuracy, providing educational researchers with expanded data collection capabilities and improved analytical precision. However, challenges such as data privacy concerns, ethical dilemmas, and the digital divide emerged as prominent issues that limit the effective integration of technology in educational research. Inferential statistics indicated a positive correlation between technology use frequency and perceived research benefits, with regression analysis showing that both the type and frequency of technology use predict research efficiency. Furthermore, ANOVA results highlighted disparities in technology adoption across educational sectors, indicating that higher education researchers tend to utilize digital tools more frequently than those in K-12 education and policy. These results underscore the need for enhanced ethical frameworks, data privacy measures, and equitable access to technology to ensure inclusive and responsible research practices. This study contributes to the discourse on technology in educational research by offering insights into both the benefits and challenges of digital tool integration and provides practical recommendations for future research in an increasingly digitalized educational landscape.